Remnant cholesterol in atherosclerotic cardiovascular disease: a systematic review and meta-analysis - Delialis, Dimitrios; Georgiopoulos, G. G.; Aivalioti, E. A.; Konstantaki, C. K.; Oikonomou, E. O.; Bampatsias, D. B.; Mavraganis, G. M.; Maneta, E. M.; Patras, R. P.; Papaioannou, M. P.; Dimopoulou, A. M. D.; Angelidakis, L. A.; et al. (European heart journal, 2023)
Accumulating evidence suggests a substantial contribution of remnant cholesterol (RC) to residual risk for the development or relapse of atherosclerotic cardiovascular disease (ASCVD).We aimed to evaluate the association of RC levels with ASCVD risk by different risk categories and method of RC assessment. We also assessed available evidence on the effect of lipid-lowering therapies (LLTs) on RC levels.Data sources: English-language searches of Medline, Pubmed and Embase (inception to 31 January 2023); ClinicalTrials.gov (October 2021); and reference lists of studies and reviews.Study selection: Studies reporting on the risk of the composite endpoint [all-cause mortality, cardiovascular mortality, and major adverse cardiac events (MACE)] by RC levels. Moreover, we searched for studies reporting differences in RC levels after administration of LLT(s).Data extraction: Dual extraction and quality assessment of individual studies.Data synthesis: Among n=29 studies with 257,387 participants, we found a pooled linear (pooled HR:1.27 per 1-SD increase,95% CI:1.12-1.43,P<0.001,I2=95%,n=15 studies) and non-linear association (pooled HR:1.59 per quartile increase,95% CI:1.35-1.85,P<0.001,I2=87.9%,n=15 studies) of RC levels and the risk of MACE both in patients with and without established ASCVD. Interestingly, the risk of MACE was higher in studies with directly measured vs. calculated RC levels. In a limited number of studies and participants, LLTs reduced RC levels.Limitation: Publication bias and heterogeneity regarding the number of participants per study, follow-up duration, ASCVD prevalence, measurement of RC levels and endpoints.RC levels are associated with ASCVD risk both in primary and secondary prevention. Directly measured RC levels are associated with ASCVD risk more evidently. Available LLTs tend to decrease RC levels, although the clinical relevance of RC decrease merits further investigation.